Curriculum Dynamics: Scientific Approach Model in Early Childhood Education Learning in ERA Towards 5.0 - Halifah, Syarifah; Halik, Abdul; Razak, Rasmida (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to design a learning system that characterizes the institution by continuously implementing a scientific approach. The type of research is descriptive qualitative with a Research and Development (R & D) approach with the ADDIE model. This study shows the factuality in the world of ECE education using a scientific approach, it turns out that educators still have difficulty understanding and implementing the scientific approach due to the influence of the educator's load, comfortable with the condition of the group or area curve, using learning with the teacher's lecture method so that a simple concept is formulated in implementing the scientific approach in ECE learning, namely designing RPPH and providing a postman book as a reference to strengthen the scientific concept in Raudhatul Athfal institutions throughout Ajattapareng. The scientific approach is an aspect of learning instilled in creative and innovative children and trains independence from an early age.